2022
DOI: 10.1177/15347354221098983
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for Cancer-Related Cognitive Impairment: A Clinical Feasibility Study

Abstract: Background: Cancer-related cognitive impairment (CRCI) is a significant problem for cancer patients, as the number of cancer survivors experiencing cognitive impairments is increasing in the absence of standard treatment. There have been attempts to improve the cognitive function of patients with cancer using acupuncture; however, no studies have been conducted using electroacupuncture. Thus, we designed a preliminary study to investigate the feasibility of a clinical trial using electroacupuncture in CRCI pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Breast cancer survivors (BCs) were recruited in this research at the Second Hospital of Anhui Medical University. The inclusion criteria were as follows: (1) aged more than 20 to under 73 years; (2) breast cancer diagnosed in adulthood; (3) FACT‐Cog‐PCI score < 63 27 , 28 ; (4) The patient complains of cognitive impairment after receiving conventional‐dose taxane‐ or anthracycline‐based chemotherapy. Exclusion criteria included history of other cancers, psychological disorders and dementia.…”
Section: Methodsmentioning
confidence: 99%
“…Breast cancer survivors (BCs) were recruited in this research at the Second Hospital of Anhui Medical University. The inclusion criteria were as follows: (1) aged more than 20 to under 73 years; (2) breast cancer diagnosed in adulthood; (3) FACT‐Cog‐PCI score < 63 27 , 28 ; (4) The patient complains of cognitive impairment after receiving conventional‐dose taxane‐ or anthracycline‐based chemotherapy. Exclusion criteria included history of other cancers, psychological disorders and dementia.…”
Section: Methodsmentioning
confidence: 99%
“…(2) Perceived cognitive impairment (PCI) score in FACT-Cog reflects CRCI. 19,20 Complaints of decreased attention and memory function after chemotherapy. (3) Karnofsky performance status (KPS) score ≥80.…”
Section: Methodsmentioning
confidence: 99%
“…Electroacupuncture (EA) is an effective family member of combo acupoint stimulation [13]. Lyu et al [14] reported that EA could be effective in alleviating various side effects caused by anticancer drugs, such as pain, vomiting, fever, fatigue, dry mouth, anxiety, depression, and insomnia. In addition, EA could promote the rehabilitation of pathological microstructures in the brain and improve the cognitive ability of patients with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EA could promote the rehabilitation of pathological microstructures in the brain and improve the cognitive ability of patients with cognitive impairment. Clinical trials [14,15] of acupuncture for preventing and managing mild cognitive impairment in older adults show that it can improve the clinical efficacy rate, Mini-Mental State Examination Scale score, Montreal Cognitive Assessment (MoCA) test score, and clock drawing task scores, suggesting that acupuncture can be an effective approach complementary to existing therapies. Evidences [14] from acupuncture in patients after an ischemic stroke support its role in the treatment of neurological deficits through modulation of neuroplasticity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation